Study of vibration in a Formula SAE vehicle through simulation - Galvão, Caio Vinícius Andrade; Brito, Halane Maria Braga Fernandes (Research, Society and Development, 2024)
This article aims to analyze the influence of the Yamaha XT660R engine vibrations on an FSAE tubular chassis using computational simulations. In these simulations, finite element software was used for modal analysis, identifying the critical vibration modes of the chassis and its natural frequencies. The results indicate vibration modes that may coincide with the operational frequencies of the engine, highlighting the need for structural modifications to mitigate potential failures. This study not only provides a theoretical basis for future experimental validations but also offers practical recommendations to improve the design of competition vehicles, contributing to safety and performance.